Futures Trading Business Opportunities and Feasibility (Gold Micro Account) at PT. Agrodana Futures as an Alternative Business Opportunity for Small Entrepreneurs - Awangga, Panji Guniwa Aria; Supriyoso, Patria (Economic: Journal Economic and Business, 2022)
There are many business or business opportunities in Indonesia that are actually attractive, promising and have legality from the government and have legal force based on the law, but many do not know about these business opportunities. One of them is Business in the Field of Trading / Futures Trading or Trading on the Exchange. This business can be an alternative choice for small entrepreneurs. Trading / Futures Trading is growing rapidly in Indonesia. Apart from offering huge profits, technological developments are also very supportive of the booming world of trading. Business people can transact anywhere and anytime. on the condition that it is not too complicated and the capital is not too large. All of that is an extraordinary magnet for anyone who wants to enter the world of trading. Behind all the conveniences and the lure of very attractive profits, lies a very large risk as well. The risk is that the capital can run out in a short time in the Trading Market. This is not caused by ignorance, but is often caused by not wanting to know the risk. Business people focus on thinking about the benefits they get. Another reason for working in this field, business people are obsessed with returning the capital that has been taken by the market. However, actually the Business Opportunity in the field of Trading is very helpful for the community in increasing the income from the capital they have, developing it, meeting operational needs and other needs, certain goals are even inherited. With the right Innovation Strategy, measurable planning and evaluation as well as organized risk management, plus a SWOT model to find out how the opportunities, strengths, threats and weaknesses faced by these small business actors/entrepreneurs at PT. Agrodana Futures and future projections for this business.